2019
DOI: 10.1097/md.0000000000015836
|View full text |Cite
|
Sign up to set email alerts
|

The association between occupational stress and psychosomatic wellbeing among Chinese nurses

Abstract: Occupational stress impairs nurses’ psychosomatic wellbeing, which includes anxiety, depression, sleep quality, and somatic symptoms; however, few studies have focused on the associations between the subdimensions of occupational stress [workload and time pressure (WTP), professional and career issues (PC), patient care and interaction (PCI), interpersonal relationships and management problems (IRMP), resource and environment problem (REP)] and psychosomatic wellbeing among nurses in China. This study thus exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
62
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 22 publications
(21 reference statements)
6
62
0
3
Order By: Relevance
“…We found that the subjective psychological stress regarding 2019-nCoV infections was positively related to daytime dysfunction and total PSQI scores. These results were comparable to those reported previously for healthcare professionals in similar studies [ [15] , [16] , [17] ]. Psychological distress and concerns about the illness may be either a cause or a consequence of poor sleep or daytime dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the subjective psychological stress regarding 2019-nCoV infections was positively related to daytime dysfunction and total PSQI scores. These results were comparable to those reported previously for healthcare professionals in similar studies [ [15] , [16] , [17] ]. Psychological distress and concerns about the illness may be either a cause or a consequence of poor sleep or daytime dysfunction.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that emotional disorders, such as depression or anxiety predict the appearance of somatic symptoms which worsen the individual's health, and this in turn, leads to new states of anxiety and somatization ( Berghoff, Tull, DiLillo, Messman-Moore, & Gratz, 2017 ; Creed, Tomenson, Chew-Graham, Macfarlane, & McBeth, 2018 ). The decreased psychosomatic health of nurses will also generate a negative influence on health care performance ( Gu et al, 2019 ; Johnson et al, 2018 ). In this study, female gender was one of the risk factors of somatic symptoms, which is consistent with previous studies ( Barsky, Peekna, & Borus, 2001 ; Halbreich & Kahn, 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since mental health is closely linked with the level of self‐perceived stress (Gu, Tan, & Zhao, 2019), we surveyed stressors and their incidence rates. The highest scoring items in T 1 were a large infected population, high infectivity; worried about family's health status; and high mortality if not treated in time.…”
Section: Discussionmentioning
confidence: 99%